Multi-exon deletions of the PKHD1 gene cause autosomal recessive polycystic kidney disease (ARPKD). Issue 10 (30th September 2005) - Bergmann, C; Küpper, F; Schmitt, C P; Vester, U; Neuhaus, T J; Senderek, J; Zerres, K
Abstract : Background: Autosomal recessive polycystic kidney disease (ARPKD) is caused by mutations in the PKHD1 (polycystic kidney and hepatic disease 1) gene on chromosome 6p12, a large gene spanning 470 kb of genomic DNA. So far, only micromutations in the 66 exons encoding the longest open reading frame (ORF) have been described, and account for about 80% of mutations. Objective: To test the hypothesis that gross genomic rearrangements and mutations in alternatively spliced exons contribute to a subset of the remaining disease alleles. Methods: Using DHPLC for alternatively spliced exons and quantitative real time polymerase chain reaction to detect genomic imbalances, 58 ARPKD patients were screened, of whom 55 were known to harbour one PKHD1 point mutation in the longest ORF. Results: Three different heterozygous PKHD1 deletions and several single nucleotide changes in alternatively spliced exons were identified. The detected partial gene deletions are most likely pathogenic, while a potential biological function of the alterations identified in alternatively spliced exons must await the definition of transcripts containing alternative exons and their predicted reading frames. Conclusions: Gross PKHD1 deletions account for a detectable proportion of ARPKD cases. Screening for major genomic PKHD1 rearrangements will further improve mutation analysis in ARPKD.